2015
DOI: 10.1002/marc.201500485
|View full text |Cite
|
Sign up to set email alerts
|

Autonomously Sensing Hydrogels for the Rapid and Selective Detection of Pathogenic Bacteria

Abstract: The development of a versatile approach for the rapid and sensitive detection of relevant pathogenic bacteria and autonomous signaling of the detection events in reporter hydrogel film coatings is reported. Exploiting chitosan hydrogel films equipped with chromogenic or fluorogenic reporter moieties, the presence of the Gram-negative bacterium Pseudomonas aeruginosa and the Gram-positive bacterium Staphylococcus aureus is sensed within 1 h by detecting the characteristic enzymes α-glucosidase and elastase with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 37 publications
2
46
2
Order By: Relevance
“…Giovanni et al 24 Here we report on the expansion of our previously introduced autonomously sensing hydrogel approach for the simple in situ and selective detection of a potentially life-threatening biosafety level 3 food pathogen. 31,32 To detect the pathogenic E. coli (EHEC) and to differentiate it from non-pathogenic E. coli (K12), the differences in enzyme secretion of these bacteria strains is 12…”
Section: Introductionmentioning
confidence: 99%
“…Giovanni et al 24 Here we report on the expansion of our previously introduced autonomously sensing hydrogel approach for the simple in situ and selective detection of a potentially life-threatening biosafety level 3 food pathogen. 31,32 To detect the pathogenic E. coli (EHEC) and to differentiate it from non-pathogenic E. coli (K12), the differences in enzyme secretion of these bacteria strains is 12…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed to detect the status of a wound through the biochemical or physical markers of the wound healing process. For example, chitosan hydrogel film with a chromogenic or fluorescent reporter moiety have been used to detect Gram‐negative Pseudomonas aeruginosa and Gram‐positive Staphylococcus aureus within 1 hour . A new method has been developed to detect the microbiological state of wound dressings; this dressing responds to the microbial environment of the wound by simple color changes and antibacterial agents.…”
Section: Methodsmentioning
confidence: 99%
“…The PDMS mask was prepared according to previous work . The PDMS prepolymer and curing agent (Sylgard ® 184) were mixed in a 10:1 by weight ratio and poured into a polystyrene Petri dish after 30 min degassing.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was shown that this approach can be expanded to application in selective assays, e.g. to differentiate Staphylococcus aureus from Pseudomonas aeruginosa (with clear medical relevance) or to differentiate the S‐1 level E. coli ( K12 ) from the S‐3 level pathogenic E. coli EHEC (with implications for food safety) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation